Immunohistochemical profile and its association with clinicopathological parameters in carcinoma breast: a prospective study in central India - Walke, Vaishali; Gunjkar, Gajanan (International Journal of Research in Medical Sciences, 2019)
Background: Carcinoma breast is one of the most common malignancies of women in India. The current study was conducted with the objective of assessing estrogen receptor (ER), progesterone receptor (PR), Her-2/neu (human epidermal growth factor receptor-2) expression and Ki67 index of breast carcinomas and its correlation with histological grade, tumour size and lymph node metastasis. Methods: Forty-seven lumpectomy or modified mastectomy specimens diagnosed as Infiltrating duct carcinoma (IDC): NOS, were selected for panel of imuno histochemistry (IHC) markers on tissue microarray blocks prepared from each case. Results: Maximum of our patients belonged to premenopausal 24/47 (51%) and 20% to younger age group (<30 year). Tumour size of 2-5 cm was observed in maximum females 29 (61%); while 13(27%) had size >5.0cm. The majority of cases diagnosed as grade I (40%) and lymph node involvement was seen in 31/47 (65%). Molecular classification revealed 10 (21%) luminal A, 4 (8%) luminal B, 9 (19%) Her2/neu positive, while triple negative phenotype comprised of maximum 24 (51%) patients. Most of the Luminal group tumours were low grade (14/15); while majority of Her2/neu positive 7/9(77%) and triple negative tumours 19/24 (80%) belonged to higher grades. Conclusions: Breast carcinoma among our patient is characterized by a large percentage of triple negative phenotype that is less susceptible to hormonal therapy. The empirical treatment with tamoxifen should therefore be reconsidered as it would be less effective. Assessment of prognostic markers in breast carcinoma is strongly advocated in order to provide the best therapeutic options.